Comparing the frequency of isotretinoin-induced hair loss at <0.5-mg/kg/d versus ≥0.5-mg/kg/d dosing in acne patients: A systematic reviewCapsule Summary - Yuliya Lytvyn, PhD; Katherine McDonald, MD; Asfandyar Mufti, MD; Jennifer Beecker, MD, CCFP (EM) (Elsevier, 2022)
Over 1 million isotretinoin prescriptions are authorized in the United States per year. An insight into the frequency, dose dependency, timing, and reversibility of hair loss associated with isotretinoin treatment for acne vulgaris could help guide dosing regimens and patient counseling. The objective of this systematic review was to assess the frequency of hair loss in patients with acne vulgaris on <0.5 mg/kg/d daily doses of isotretinoin versus the frequency of hair loss in patients with acne vulgaris on ≥0.5 mg/kg/d daily doses of isotretinoin.An Embase and MEDLINE search was conducted on July 15, 2020, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The review focused on acne vulgaris patients. The treatment of acne vulgaris is the most common use of isotretinoin, and the population is typically younger and with fewer comorbidities.Twenty-two studies reported hair loss with oral isotretinoin treatment. A frequency analysis suggested that patients with acne vulgaris on <0.5 mg/kg/d of isotretinoin experienced hair loss at a frequency of 3.2% (n = 18/565) compared with those on ≥0.5 mg/kg/d, who experienced hair loss at a frequency of 5.7% (n = 192/3375). Inferential statistics were not possible.Physicians should consider counseling patients about the risk of telogen effluvium prior to drug initiation, as is commonly done for other side effects. The potential trend of increased hair loss frequency at a higher daily dosing warrants further investigation using higher-quality research.